3D chick embryo chorioallantoic membrane model as an in vivo model to study morphological and histopathological features of feline fibrosarcomas - Zabielska-Koczywąs, Katarzyna (BMC Vet Res, 2017)
BACKGROUND: The chick embryo chorioallantoic membrane (CAM) model is well described in human medicine as a cost-effective, easy to perform preclinical oncological model for observing pro- and antiangiogenic response, tumor biology and metastasis. The main objective of this article was to present the modification of the CAM assay in order to evaluate tumor growth from two feline fibrosarcoma cell lines (FFS1, FFS3) and describe their morphological and histopathological features. RESULTS: The authors described morphological and histopathological features of two feline fibrosarcoma cell lines (FFS1 and FFS3) grown on the CAM. Tumors from the FFS1 cell line showed high malignancy (grade III), while tumors from the FFS3 cell line were grade II. Proliferation markers (Ki-67 and PCNA) were determined and the positive correlation between PCNA and tumor grade (r = 0.8247; p < 0.001) was demonstrated, as opposed to Ki-67. CONCLUSIONS: The results obtained indicate that PCNA may be helpful to evaluate the tumor grade, better than Ki-67, for feline fibrosarcomas. However, further investigations of proliferation marker, in bigger number of feline spontaneous fibrosarcomas and feline fibrosarcomas grown on the CAM from different cell lines, are needed to confirm these observations.